GESTURE, MIMESIS AND IMAGE: ADORNO, BENJAMIN AND THE GUITAR MUSIC OF BRIAN FERNEYHOUGH. (28th September 2016) - Castro-Magas, Diego
Abstract: One important stimulus in attempting to apply Adorno's constellation of concepts on performance to Brian Ferneyhough's guitar music is that both display the influence of Walter Benjamin's thought. Benjamin's concept of mimesis influenced Adorno's theory of musical reproduction, however much Adorno may have reformulated it, and various Benjaminian topics are traceable in Ferneyhough's guitar music, especially Kurze Schatten II (1983–89) for solo guitar. Adorno claims that true reproduction is the X-ray image of the work of music, a rendition of all the aspects that lie hidden beneath the surface. By exploring the conceptual traces of Benjamin's thought in Kurze Schatten II, this article examines how performer's interpretative choices are likely to render the X-ray image of this music in performance, as seen through a gesture-based approach.